Radiation dose for normal organs by helical tomotherapy for lung cancer. (August 2015) - Tseng, Hsien-Chun; Liu, Wen-Shan; Tsai, Hsiao-Han; Chu, Hsin-Yi; Lin, Jye-Bin; Chen, Chien-Yi
Abstract: This study derived a simple equation of effective dose ( E ) versus normal organ of patients with varying body weights undergoing lung cancer treatment of helical tomotherapy (TOMO). Five tissue-equivalent and Rando phantoms were used to simulate lung cancer patients. This study then measured E and equivalent dose of organ or tissues ( D T ) using thermoluminescent dosimetry (TLD-100H). The TLD-100H was calibrated using TOMO 6 MV photons, then inserted into phantom positions that closely corresponded with the position of the represented organs and tissues. Both E and D T were evaluated by ICRP 103. Peripheral doses varied markedly at positions close to the tumor center. The maximum statistical and total errors were 16.7–22.3%. This analytical result indicates that E of Rando and tissue-equivalent phantoms was in the ranged of 9.44±1.70 (10 kg) to 4.58±0.83 (90 kg) mSv/Gy. Notably, E decreased exponentially as phantom weight increased. Peripheral doses were also evaluated by TLD as a function of distance from the tumor center. Finally, experimental results are compared with those in literature. These findings will prove useful to patients, physicians, radiologists, and the public. Highlights: Phantoms were used to measure effective dose of helical tomotherapy. TLDs inserted into five varying body weights phantoms. Both effective dose and equivalent dose of organ were evaluated by ICRP 103. Effective dose decreased exponentially as phantom weight increased. Peripheral doses varied markedly close to the tumor center.